TRADISI SENGKOLAN KANONG SEBELUM MELAHIRKAN PADA MASYARAKAT MELAYU DESA NANGA MAHAP DALAM KAJIAN URF - Isnaini, Baihaqi; Bakar, Abu; Rahmiani , Nur (Al-Usroh, 2025)
This research aims to examine and analyze the Sengkolan Kanong tradition carried out by the Malay community in Nanga Mahap Village, Sekadau Regency, from the perspective of 'urf. Using a qualitative method, this study applies a field research approach to collect primary data through in-depth interviews with practitioners, community leaders, and religious figures, as well as secondary data from literature review. The collected data were then analyzed through the stages of data compression, structured data presentation, and conclusion drawing. The results show that the Sengkolan Kanong tradition is a series of symbolic rituals involving the use of fresh flour and coconut leaves, accompanied by the recitation of Islamic prayers. This tradition has important cultural and spiritual values, and also serves to strengthen family relationships. From an 'urf perspective, this tradition can be categorized as 'urf shahih because most of its practices are in line with Islamic law, but there are some elements of local culture, such as khurafat (superstition) and exposed aurat, that need to be adjusted. This study concludes that the Sengkolan Kanong tradition has positive values and can be maintained, as long as aspects that conflict with Islamic law are continuously monitored and adjusted.